Hi,

I need to get from

[(1-p)f+p(1-f)](1+v)-[(1-p)(1-f)+pf] = x

to (2+v)(f+p-2pf)-1 = x

but I'm stuck. I'd appreciate any tips on what I should I do after the following.

(f+p-2pf)(1+v) + (f + p - 2pf) - 1 = x

Thanks in advance.

- Fri Jul 05, 2013 2:10 pm
- Forum: Beginning Algebra
- Topic: Stuck on rearranging of this equation
- Replies:
**1** - Views:
**1438**

Hi,

I need to get from

[(1-p)f+p(1-f)](1+v)-[(1-p)(1-f)+pf] = x

to (2+v)(f+p-2pf)-1 = x

but I'm stuck. I'd appreciate any tips on what I should I do after the following.

(f+p-2pf)(1+v) + (f + p - 2pf) - 1 = x

Thanks in advance.

I need to get from

[(1-p)f+p(1-f)](1+v)-[(1-p)(1-f)+pf] = x

to (2+v)(f+p-2pf)-1 = x

but I'm stuck. I'd appreciate any tips on what I should I do after the following.

(f+p-2pf)(1+v) + (f + p - 2pf) - 1 = x

Thanks in advance.